(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of laser acupuncture combined with exercise therapy on NDI score changes in patients with cervical spondylosis. Subjects and Methods: Thirty patients diagnosed with cervical spondylosis were treated with laser acupuncture and exercise therapy for four weeks. Study design: Clinical trial comparing pre- and post-treatment results in a single group of subjects, conducted at the Department of Physical Therapy and Rehabilitation, Lê Văn Thịnh Hospital, from February 2024 to May 2024. Results: After four weeks, the total NDI score decreased from 20 (19-21) to 13 (11-14), with pain intensity reducing to 1 (0-2), headache to 1 (0-1), concentration to 1 (1-2), lifting heavy objects to 2 (1-2), work to 1 (1-2), driving to 2 (1-2), recreation to 2 (2-2), personal care to 0.5 (0-1), and reading to 1 (1-2). Conclusion: After four weeks of study, the NDI scores of patients significantly improved with the use of laser acupuncture combined with exercise therapy, with no reported side effects.